VAK-therapy as a variant of local treatment of destructive forms of erysipelas - S. D. Shapoval; L. A. Vasylevska; V. O. Bielinska (Сучасні медичні технології)
Purpose of the study. Improve postoperative treatment of phlegmonous and necrotic forms of erysipelas by alternating HAC therapy of wounds and staged necrectomies, reduce the time of cleaning and preparation of the wound for dermatoplasty.